A case study of thermal analysis of a solar assisted absorption air-conditioning system using R-410A for domestic applications. (August 2021) - Rahman, Areeba; Abas, Naeem; Dilshad, Saad; Saleem, Muhammad Shoaib
Abstract: Sustainable future and green environment goals quest for the development of technologies to utilize renewable energy resources to power the people. This study focuses on the designing, modelling, and simulation of an absorption solar air-conditioning system. Key performance parameters are identified, optimized for maximum efficiency and simulated in transient energy simulation software TRNSYS ®. The designed model comprises five thermal loops: a solar loop consisting of an evacuated glass tube solar collector having R-410A as heat transfer fluid in it and a heat exchanger heat tank, second loop has an absorption chiller, and an auxiliary furnace with hot water stream, third is the cooling tower loop, the fourth loop is of chilled water from the chiller and the final thermal loop is for air delivery of cooling to each room. The system is simulated using Lahore, Pakistan's climate conditions and offered a good tendency for the proposed system to meet air-conditioning demand at the domestic level. The average collector outlet temperature value of 78 °C has been recorded throughout the week. Collector provides useful energy gain at an average rate of 71, 065 kJ/h. Average storage tank temperature at the outlet of heat exchanger is 92°C. Average room temperature values of three rooms are 27°C, 30°C and 19°C respectively.